2014
DOI: 10.3144/expresspolymlett.2014.90
|View full text |Cite
|
Sign up to set email alerts
|

Role of surfactant molecular weight on morphology and properties of functionalized graphite oxide filled polypropylene nanocomposites

Abstract: Conductive polymer composites have aroused wide interests from both academia and industry in the field of functional materials. Addition of diverse conducting fillers such as carbon black [1,2], graphite [3], and metal fiber or powder [4] into thermoplastic polymers through melt mixing is an effective approach to fabricate conductive composites. Because a great amount of the fillers, generally greater than 15 wt% [5], were required for the host polymer to become conductive, resulting in both poor processabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…This shift up of T c is beneficial from an industrial point of view since it implies shorter cycle times during processing. This nucleation effect has been also observed in other iPPs composites incorporating different types of graphene or derivatives [24,[38][39][40][41]56,57]. The subsequent second melting curves are rather similar in both shape and T m location for all the different samples, independently of the type of nanofiber incorporated, GHS or GLS.…”
Section: Thermal Stability and Phase Transitionssupporting
confidence: 73%
“…This shift up of T c is beneficial from an industrial point of view since it implies shorter cycle times during processing. This nucleation effect has been also observed in other iPPs composites incorporating different types of graphene or derivatives [24,[38][39][40][41]56,57]. The subsequent second melting curves are rather similar in both shape and T m location for all the different samples, independently of the type of nanofiber incorporated, GHS or GLS.…”
Section: Thermal Stability and Phase Transitionssupporting
confidence: 73%
“…Inherent to the success of the iPP based micro and nanocomposites is the need to assure that the desired interface performance remains available during the manufacturing and scaling compounding operations up to the macro (or final application) level of these composite materials. Indeed, the development of cheap and efficient interface agents obtained by grafting of an optimum number maleic anhydride like polar groups into the iPP backbone continues (from early developments) as one of the most competitive ways to optimize the mechanical performance of those engineering materials …”
Section: Introductionmentioning
confidence: 99%
“…However, the viscosity of the HPP/NA-21 blend is lower than that of the HPP/NA-11 blend, since the interaction force between the molecular chains becomes weak due to the addition of NA-11. The sodium laurate components in NA-21 combine with the macromolecular chains through hydrogen bonding, which leads to more negative charge with large molecular chains, electrostatic repulsion and steric hindrance, resulting in the macromolecular stretch and the chain tangles weakening [41]. According to the molecular weight test results, it is also found that the effect of NA-21 on reducing intermolecular entanglement is more significant than NA-11, whether in HPP or LPP.…”
Section: Rheological Behaviorsmentioning
confidence: 99%